65.8k views
0 votes
If f(x) = log↓2 (x + 4), what is f↑−1(3)

1 Answer

6 votes
as you already know, to get the inverse of any expression, we start off by doing a switch on the variables, and then we solve for "y".


\bf \textit{Logarithm Cancellation Rules} \\\\ log_a a^x = x\qquad \qquad a^(log_a x)=x\\\\ -------------------------------\\\\ \stackrel{f(x)}{\underline{y}}=log_2(x+4)\qquad \qquad \stackrel{inverse}{x=log_2(\underline{y}+4)} \\\\\\ 2^x=2^(log_2(y+4))\implies 2^x=y+4\implies 2^x-4=\stackrel{f^(-1)(x)}{y} \\\\\\ 2^3-4=f^(-1)(3)\implies 8-4=f^(-1)(3)\implies 4=f^(-1)(3)
User Alberto De Paola
by
5.6k points